2017
DOI: 10.3171/2017.3.focus1742
|View full text |Cite
|
Sign up to set email alerts
|

Off-label uses of the Pipeline embolization device: a review of the literature

Abstract: The Pipeline embolization device (PED) is the most widely used flow diverter in endovascular neurosurgery. In 2011, the device received FDA approval for the treatment of large and giant aneurysms in the internal carotid artery extending from the petrous to the superior hypophyseal segments. However, as popularity of the device grew and neurosurgeons gained more experience, its use has extended to several other indications. Some of these off-label uses include previously treated aneurysms, acutely ruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 69 publications
2
65
0
Order By: Relevance
“…There are also studies presenting data on different locations of the aneurysm in the intracranial circulation 3. Moreover in 2017 Bescke et al reported the results of a five-year follow-up of complex internal carotid artery aneurysms treated with the Pipeline Embolization Device (PED) for uncoilable and failed aneurysms, and demonstrated that the aneurysm occlusion at angiographic follow-up was progressively increasing over time 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also studies presenting data on different locations of the aneurysm in the intracranial circulation 3. Moreover in 2017 Bescke et al reported the results of a five-year follow-up of complex internal carotid artery aneurysms treated with the Pipeline Embolization Device (PED) for uncoilable and failed aneurysms, and demonstrated that the aneurysm occlusion at angiographic follow-up was progressively increasing over time 8…”
Section: Discussionmentioning
confidence: 99%
“…Based on their ability to reconstruct the parent artery, indications of their use are constantly extending from giant aneurysms to small aneurysms and to aneurysms located on small vessels 3. Innovation including improved cathether technology and simplified device delivery systems have enabled more distal treatment above the circle of Willis and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, complete occlusion rate at the latest follow-up of dissecting aneurysms treated with a PED was approximately 70% 9. Considering that these aneurysms are characterized by a dynamic behavior, careful follow-up is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pre-bifurcation M1 length is also a critical consideration, as to avoid intrusion of the FD into the MCA bifurcation in a short M1 segment, jailing one of the M2s. Lastly, the M1 segment contains critical lenticulostriate vessels26; while these have been shown to be safely jailed,27 it should ideally be minimized.…”
Section: Discussionmentioning
confidence: 99%